2018
DOI: 10.3389/fneur.2018.00605
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Microglial Activation by Adenosine A2a Receptor in Animal Models of Perinatal Brain Injury

Abstract: Neuroinflammation has a key role in the pathogenesis of perinatal brain injury. Caffeine, a nonspecific antagonist of adenosine receptors (ARs), is widely used to treat apnea of prematurity and has been linked to a decrease in the incidence of cerebral palsy in premature infants. The mechanisms explaining its neuroprotective effect have not yet been elucidated. The objective of this study was to characterize the expression of adenosine and ARs in two neonatal rat models of neuroinflammation and to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 54 publications
6
44
0
Order By: Relevance
“…Even though this reduced inflammation could be the result of a contained lesion due to the caffeine treatment, a direct caffeine-induced modulation in microglia has been suggested. Recent findings have demonstrated that adenosine agonists in microglia culture lead to an increase of M1 marker expression [34], and moreover, activation of the A2aR in microglia was associated with cytokine release and process retraction in vivo suggestive of an activation state [35,36]. In contrast, caffeine suppresses the generation of proinflammatory mediators [37], and the blockade of A2aR was indeed reported to reduce microglial activation both in vivo and in vitro [38], thus confirming the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…Even though this reduced inflammation could be the result of a contained lesion due to the caffeine treatment, a direct caffeine-induced modulation in microglia has been suggested. Recent findings have demonstrated that adenosine agonists in microglia culture lead to an increase of M1 marker expression [34], and moreover, activation of the A2aR in microglia was associated with cytokine release and process retraction in vivo suggestive of an activation state [35,36]. In contrast, caffeine suppresses the generation of proinflammatory mediators [37], and the blockade of A2aR was indeed reported to reduce microglial activation both in vivo and in vitro [38], thus confirming the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…Antioxidants 2020, 9, x FOR PEER REVIEW 6 of 21 inflammatory cytokines [105], and changes the microglia into amoeboid shapes [106]. Conversely, A2AR antagonists suppress microglia activation, as highlighted previously [104]. Figure 2 depicts the role of A2A in AD.…”
Section: Pathological Bases Of Oxidative Stress and Neuroinflammationmentioning
confidence: 86%
“…Nrf2 induces the expression of antioxidants and cytoprotective genes, which provoke an anti-inflammatory response that is critical for the healing process [103]. Apart from the different sorts of kinases (like MAP kinases), there are some receptors such as adenosine receptors that play a role in neuroinflammation, such as adenosine A2A receptors [104]. At the microglial level, the expression of A2AR is usually low; it activates with brain insults and facilitates the release of the inflammatory cytokines [105], and changes the microglia into amoeboid shapes [106].…”
Section: Pathophysiology Of Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…The enhancement of neuroinflammatory reactions after perinatal brain injury was observed in rats due to A2AR activation and the consequent upregulation of M1 microglial markers (IL-β, IL-6); an antagonist of A2ARs was beneficial under these conditions [156]. Developmental risk factors, such as the exposure of high levels of glucocorticoids, may contribute to the pathogenesis of anxiety disorders [157].…”
Section: A2a and A2b Receptorsmentioning
confidence: 99%